1988
DOI: 10.1159/000234649
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Exposure to the Beta-Adrenergic Receptor-Blocking Agent Metoprolol and Allergy

Abstract: Cord blood IgE levels and the development of allergy were studied in 29 children born by mothers who had been treated with the β-adrenergic receptor blocking agent, metoprolol, during the pregnancy and in 23 children of placebo-treated mothers. In 13 (45%) of the former and 3 (15%) of the placebo group elevated cord blood IgE levels, i.e. more than 0.9 kU/l and/or obvious or probable allergy developed (p = 0.03). The findings support previous experimental observations that β-blocking agents may enhance IgE ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Males have higher neonatal IgE concentrations than girls and season of birth may have some influence on the IgE level, not only in mothers but also in their new-born babies (20,25,26). Maternal intake of some drugs (progesterone, beta-blockers) seems to increase neonatal IgE concentrations (16,34). Maternal smoking seems to affect cord blood IgE concentrations in accordance with a similar dose-response reported in adult smokers (35), i.e.…”
supporting
confidence: 65%
“…Males have higher neonatal IgE concentrations than girls and season of birth may have some influence on the IgE level, not only in mothers but also in their new-born babies (20,25,26). Maternal intake of some drugs (progesterone, beta-blockers) seems to increase neonatal IgE concentrations (16,34). Maternal smoking seems to affect cord blood IgE concentrations in accordance with a similar dose-response reported in adult smokers (35), i.e.…”
supporting
confidence: 65%
“…Recently, umbilical artery flow velocity from Doppler ultrasound was found to be significantly reduced at 18 weeks' gestation in moderately and severely asthmatic mothers (162). Intrauterine exposure to beta agonists (163) and poorly managed maternal asthma (164,165) have been associated with asthma development in children, but the independent effects of each have not been disentangled. These risk factors may contribute significantly to the burden of asthma, because 3.7-8.4 percent of US pregnancies have been estimated to be affected by maternal asthma (166).…”
Section: Intrauterine Risk Factors For Atopy and Asthma Developmentmentioning
confidence: 99%
“…However, these elevated levels were not associated with an increased development of atopic disease in the infants [16]. Bjorksten et al [17] found that the B-blocking agent metoprolol, intake during pregnancy, significantly increased the appearance of elevated neonatal IgE concentrations and the development of atopic symptoms before 18 months of age.…”
Section: Prenatal Factorsmentioning
confidence: 99%